Fixed point Results on a Complete Soft Usual Metric Space - Ramakant Bhardwaj, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present work is related to the theory of fixed point in complete soft usual metric space, which are extension of well-known results on complete metric space as well as complete soft metric space. The obtained results can be used in decision making as well as based on uncertainty problems. Soft weak contractive mapping and soft generalized weak contractive mapping are used to obtained the results.